PEMETAAN TATA KELOLA INFRASTRUKTUR PENYIARAN RADIO SWASTA DI DKI JAKARTA - Haryono, Cosmas Gatot; Pamungkas, Thomas Bambang (Islamic Communication Journal, 2020)
The aims of this study is to conduct mapping related to the implementation of governance of private radio broadcasting in DKI Jakarta. This is interesting to do because there are many complaints from the public that the management of broadcast media in Jakarta, especially the Radio Private Broadcasting Institutions, deviates much from the rules stipulated in Law no. 32 of 2002 concerning Broadcasting. This research is a quantitative research with descriptive type that tries to see how the implementation of private radio management in Jakarta as the dependent variable. While the components seen are administrative data, broadcast program data, facilities and infrastructure development, and staffing data. The results obtained indicate that there are many irregularities in radio broadcasting management in DKI Jakarta, including related to share ownership by employees, time allocation for public service announcements, certified employees and ownership of standard infrastructure for broadcasting.